Pilot study for the modelling of congestion pricing in Kota Kinabalu, Sabah - Mohd Azizul Ladin; Siti Nurmasyittah Binti Ag Besar; Noor Sheena Herayati Harith; Nurmin Bolong; Ismail Saad; Nazaruddin Taha (2020)
Congestion pricing is a policy at which road users being charged with certain amount for using particular road during peak hours. It is as much about meeting the demand of car drivers for road space as allocating road space between road users. It has been successfully implemented in some other countries such as Stockholm, London and Singapore with various scheme of congestion pricing. Hence, the main aim of this pilot study is to evaluate and create model based on the willingness of the Kota Kinabalu City residents’ to shift to public transport due to the implementation of congestion pricing. A total of 60 respondents were randomly chosen within Kota Kinabalu City. Data collection is being conducted using stated preference survey and analysed with Microsoft Office Excel 2010 in order to conduct regression analysis and develop a logistic transport model analysis. It is found that the number of people who willing to shift to public transport is parallel with the congestion charge amount. The results from this pilot study indicate that 71.67% of respondents are willing to shift to public transport when the congestion charge price is RM4.00. This study can give contribution for further transportations planning in order to achieve sustainable transportations in Kota Kinabalu, Sabah.